Spectral responsivity measurement of photovoltaic detectors by comparison with a pyroelectric detector on individual nano-second laser pulses. (11th May 2017) - Hong, Kee-Suk; Park, Seongchong; Hwang, Jisoo; Atkinson, Errol; Manson, Peter; Lee, Dong-Hoon
Abstract: We demonstrate that the individual single pulse of a nano-second laser can be used to measure the spectral responsivity of photovoltaic detectors. With this new scheme, the relative spectral responsivity of a photodiode can be determined from the spectral reflectance of the surface of a pyroelectric detector. We also developed the adequate data acquisition procedure, which can eliminate systematic errors caused by the nonlinear pulse response. The method is experimentally demonstrated for Si and Ge photodiodes in a wide wavelength range from 420 nm to 1600 nm and verified by comparison with the method using a CW source.